A Multi-Modal Toolkit for Studying Neutrophils in Cancer and Beyond - Diana Changirwa (MDPI AG, 2021)
As key effector cells of the innate immune response, neutrophils are rapidly deployed to sites of inflammation where they deliver a payload of potent effector mechanisms that are essential for host defense against pathogens as well as tissue homeostasis. In addition, neutrophils are central contributors to the pathogenesis of a vast spectrum of inflammatory, degenerative, and neoplastic diseases. As our understanding of neutrophils in health and disease continually expands, so too does our appreciation of their complex and dynamic nature in vivo; from development, maturation, and trafficking to cellular heterogeneity and functional plasticity. Therefore, contemporary neutrophil research relies on multiple complementary methodologies to perform integrated analysis of neutrophil phenotypic heterogeneity, organ- and stimulus-specific trafficking mechanisms, as well as tailored effector functions in vivo. This review discusses established and emerging technologies used to study neutrophils, with a focus on in vivo imaging in animal models, as well as next-generation ex vivo model systems to study mechanisms of neutrophil function. Furthermore, we discuss how high-dimensional single-cell analysis technologies are driving a renaissance in neutrophil biology by redefining our understanding of neutrophil development, heterogeneity, and functional plasticity. Finally, we discuss innovative applications and emerging opportunities to integrate these high-dimensional, multi-modal techniques to deepen our understanding of neutrophils in cancer research and beyond.